THE COST EFFICIENCY AND DETERMINANTS IN SOUTHEAST ASIAN BANKING SECTOR: THE EVIDENCE OF TEN COUNTRIES AND AREAS, 1998-2012 - Li, Ruolin (2013)
The purpose of this paper is to estimate the cost efficiency scores of the banking sectors in 10 Southeast Asian countries and areas (Taiwan, Hong Kong, Malaysia, Singapore, Macao, Indonesia, China, Philippines, Thailand and South Korea) over the period of 1998-2012 using stochastic frontier analysis (SFA). The overall cost efficiency score of banking sectors in the ten Southeast Asian countries is 0.7203, indicating that the banking sector should reduce 29.97% costs to match the performance with the best practice banks. And the banking sector in Macao shows a best performance in cost efficient, with 0.8404 efficiency score, while South Korea is the least cost efficient country with the efficiency of 0.6433. At the second stage of analysis, one step regression analysis is employed to find out the determinants of cost efficiency in the sample. And the results suggest that the stock market capitalisation and equity ratio have significantly positive correlation to banks’ cost efficiency, while the bank claims to private sector and market concentration are negatively linked to cost efficient level. Finally, there is no evidence to support the real GDP growth and annual inflation statistically correlate to banks’ cost efficiency.